Design Thinking for Game-Based learning tool: Case Study on SK Kampung Rembus Primary School - Audrey Duyan, Gima (Universiti Malaysia Sarawak, (UNIMAS), 2023)
This research aims to comprehend the design thinking process that can facilitate the creation of game-based learning. Research conducted at Sekolah Kebangsaan Kampung Rembus in the city of Kota Samarahan, Sarawak. To answer this question, pre- and post-tests are administered to evaluate primary school students’ performance using the game-based learning tool. Using game-based learning techniques, it targets students in primary school who struggle to acquire new vocabulary words in a fun and engaging manner. The results can be used to demonstrate that design thinking can aid in the creation of game-based learning tools.